Exploring Factors Impacting User Satisfaction with Electronic Payment Services in Taiwan: A Text-Mining Analysis of User Reviews - Shu-Fen Tu; Ching-Sheng Hsu (Big Data and Cognitive Computing, 2025)
Electronic payments are becoming increasingly popular in Taiwan; however, there is a lack of studies examining the factors affecting user satisfaction with electronic payments in Taiwan. This study focuses on Android phone users to identify key factors influencing their experiences based on user reviews of electronic payment mobile applications. It analyzes which factors contribute to positive satisfaction and which lead to negative experiences. The study employed BERTopic for topic modeling, which flexibly accommodates multiple languages, enabling effective examination of reviews written in Chinese. Additionally, we utilized the semantic understanding capabilities of large-scale language models to preliminarily name the generated topics with the help of ChatGPT Plus. These preliminary names were then manually refined to determine the final topic titles. The findings reveal that for Android phone users, electronic payment services that enhance user convenience and offer discounts tend to foster positive satisfaction. Conversely, the instability of electronic payment applications results in many user complaints. These research results can provide valuable insights for specialized electronic payment institutions in Taiwan to enhance their services.